METABOLIC ALTERATIONS IN BANANA INDUCED BY MECHANICAL DAMAGE - Carvalho Brant Maia, Leonardo; Martins Maia, Victor; Chamhum Salomão, Luiz Carlos; Panicali Auler Salles, Barbara; Facco Pegoraro, Rodinei (Revista Unimontes Científica, 2020)
Objective: Bananas respond at the physical and physiological level to mechanical damage. Mechanical injuries cause alterations in color and flavor, tissue softening, faster ripening, increased weight loss, increased invasion of microorganisms, and higher enzyme activity in the affected area. The present study aimed was to verify the metabolic alterations in ‘Dwarf Prata’ bananas induced by mechanical stress and stored at room condition (25.4 ºC, 82% RH). Methods: Was used split-plot in time design, consisting of one control and four mechanical injury types: cutting, abrasion, impact and compression, sampled over time. Samples were collected within a period of 9 days, based on a completely randomized design with 3 replications and 3 fruits per plot. Results: The evolution of the peel color and fruit respiration were measured. The peel color grade 6 was only exceeded in fruits damaged by abrasion and impact, while the others came quite close to this grade. The greater speed of impact-damaged fruit in reaching peel color grade 6, a completely yellow peel, can be explained by the anticipation of the climacteric respiratory peak in fruits of this treatment compared to the control and the other mechanical damage types, which showed no production peak of CO2 before the control. Mechanical damage stimulates respiratory process and ethylene biosynthesis. Conclusion: The impact damage anticipated the ripening.